The Dynamics of Unhealthy Friendships and Their Impact on Students' Mental Health: A Phenomenological Case Study at State Universities in Jember Regency - Dewi, Riskha Dora Candra (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study aims to explore the dynamics of unhealthy friendships and their impact on the mental health of students at state universities in Jember Regency. Employing a qualitative phenomenological approach, the research investigates students’ subjective experiences in navigating interpersonal relationships characterized by manipulation, value suppression, and power imbalance. Data were collected through observation, documentation, in-depth interviews, and semi-structured questionnaires. The findings indicate that 78% of respondents have experienced unhealthy friendships, which significantly affect their psychological well-being, including increased stress, decreased self-confidence, sleep disturbances, diminished motivation to study, and reduced academic performance. These results underscore the need for systemic interventions by higher education institutions to raise student awareness regarding the risks of unhealthy friendships and to provide adequate psychosocial support. Recommendations include strengthening mentoring programs, peer counseling, and healthy communication education as preventive and responsive measures to foster a supportive campus social ecosystem that promotes student mental health.